Serial analyses of clinical spectra and outcomes in Chinese women with pregnancy-induced optic neuritis - Bai, Wenhao; Sun, Mingming; Song, Honglu; Li, Hongen; Xu, Xintong; Chen, Xiyun; Zhao, Yixuan; Chen, Biyue; Yao, Sheng; Xu, Quangang; Wei, Shihui; Zhou, Huanfen; et al. (Frontiers in Medicine, 2022)
Objective This study aimed to investigate the clinical spectra and outcomes in pregnancy-related optic neuritis (ON). Methods We analyzed the clinical subtype and prognosis of women with pregnancy-related ON in the neuro-ophthalmology department of the First Medical Center at the Chinese PLA General Hospital from January 2014 to December 2019. Results A total of 54 patients, including 21 (38.9%) with idiopathic ON (ION), 27 (50.0%) with aquaporin-4 (AQP4)-ON, and 6 (11.6%) with myelin oligodendrocyte glycoprotein (MOG)-ON, who experienced 58 informative pregnancies and 67 episodes of pregnancy-related ON were assessed. Among the ON attacks, there were 11 (16.4%) during pregnancy and 56 (83.6%) within 1 year postpartum (PP1) or after abortion, including 33 (49.3%) in the first trimester. In total, 14 (25.9%) patients with ON onset before pregnancy had a higher relapse rate during PP1 than within 1 year before pregnancy (p = 0.021), and 24 (85.7%) eyes with ION and nine (100%) with MOG-ON had significantly better visual outcomes (p ≥ 0.5) than those with AQP4-ON (14, 35%) (p < 0.001 and p < 0.001, respectively). Two AQP4-ON patients had premature birth and low baby weight, respectively. There were no birth defects or stillbirths. Conclusion The significantly increased relapse rate and numerous cases of ON after pregnancy suggest that delivery adversely affects the course of ON.